2012
DOI: 10.1515/ijnsns-2011-0097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging Treatment on Dynamic Behavior of Mg-Gd-Y Alloy

Abstract: Magnesium alloy is very attractive in many industrial applications due to its low density. The structure-property relationships of the magnesium alloy under quasi-static loading have been extensively investigated. However, the dynamic behavior, particularly the mechanism of high-rate plastic deformation, of the magnesium alloy requires more in-depth investigations. In this paper, the effect of aging treatment on the quasi-static and dynamic properties of a typical rare earth Mg-Gd-Y magnesium alloy is investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…6.2(f)) shows that mainly round shaped particles containing more Zr appeared in the T6 state. Similar observations were also reported by Wang et al [213]. Based on the Mg-Gd phase diagram [69,214] and Mg-Y phase diagram [215], only one single phase solid solution should appear in the Mg-10Gd-3Y-0.5Zr (GW103K) alloy during solution treatment at 500°C.…”
Section: T6 Heat Treated Gw103k Alloysupporting
confidence: 88%
See 1 more Smart Citation
“…6.2(f)) shows that mainly round shaped particles containing more Zr appeared in the T6 state. Similar observations were also reported by Wang et al [213]. Based on the Mg-Gd phase diagram [69,214] and Mg-Y phase diagram [215], only one single phase solid solution should appear in the Mg-10Gd-3Y-0.5Zr (GW103K) alloy during solution treatment at 500°C.…”
Section: T6 Heat Treated Gw103k Alloysupporting
confidence: 88%
“…6.2(c)) seemed to be higher as compared to the regular RE-rich particles in the T5 alloy due to the aging process. Wang et al [213] also reported that the square-shaped second phase particles were mostly rich with Gd and Y and round-shaped second phase particles were rich with Zr, which actually concurred with the results of the GW103K alloy in both as-extruded and T5 states.…”
Section: T5 Heat Treated Gw103k Alloysupporting
confidence: 67%